Ricercare oltre - Paolo Mottana (Firenze University Press, 2010)
Now appears quite clear that compared theoretical pedagogy is considered unnecessary. In fact it is the theoretical dimension reflective to make a science pedagogy that emancipated and continuous development. Complexity and concern are the aspects that give "greater" vitality in science teaching today even if the policies of the arrogant powers that count seem to really jeopardize the life of knowledge in their wealth. The author questions the need to rethink deeply the importance of educational research. The author questions the need to rethink deeply the importance of many categories such as «utility» that might undermine the very ability to develop creative languages and teaching.